Global top e-commerce companies: Transparency analysis based on annual reports - Ionel Bostan; Alic Bîrcă; Aliona Bîrcă; Christiana Brigitte Sandu (Journal of Risk and Financial Management, 2022)
This paper analyzes the transparency of reporting in e-commerce companies, which has a high impact on decision making. Stakeholders make sure that companies are as transparent as possible in their actions, and the information disclosed in annual reports is very credible. In this context, the highly asked for information refers to the structure of corporate governance, the activity of committees set by the board of directors, managerial strategies, human resource and sustainability policies, risks, financial reporting, financial and non-financial performance, etc. To test and validate the results of our research, we identified the 31 most efficient global e-commerce companies. For this purpose, 31 annual corporate reports were analyzed for 2019 and 2020 by extracting several independent variables: corporate governance, human resource policies, sustainable development, performance, risks and financial reporting. The results of the analysis were validated by using SmartPLS (v. 3.3.3) software.
Keywords: 650; companies/businesses; corporate governance; financial reporting; performance